SECONDARY STUDENTS’ PREFERENCES IN ACCESSING YOUTUBE VIDEOS FOR EXTENSIVE LISTENING DURING DISTANCE LEARNING - Anindita Fachrunnisa; Totoh Tauhidin Abas; Evi Karlina Ambarwati (IKIP Siliwangi, 2023)
Distance learning makes students less time spent studying from school. The various limitations found in conducting distance learning make students choose to hone their skills independently with a variety of learning resources, one of which is the YouTube application. To explore and investigate the importance of listening skills in English learning to understand students' interests in learning English listening skills prompted this research. This study aims to determine students’ preferences in acquiring listening comprehension through self-access materials in YouTube. The study used qualitative research. The data were collected by means of open-ended questionnaires and interviews. The participants were seven Indonesian high school students. It was found that the students preferred accessing listening materials through videos produced by English native speakers. In addition, students enjoy videos that use daily English. Their extensive listening practice was motivated by the structure of English class. The implication of this study will recommend teachers to create meaningful, attractive and encouraging teaching materials. Keywords: Extensive Listening; Students’ Preference; YouTube